2010
DOI: 10.1155/2010/702748
|View full text |Cite
|
Sign up to set email alerts
|

Differential Impact of Adherence to Pegylated Interferon and Ribavirin in the Treatment of Genotype 1 High Viral Titer Chronic Hepatitis C

Abstract: To clarify the impact of adherence, we treated 122 genotype 1 high viral titer chronic hepatitis C patients with pegylated interferon (peg-IFN) and ribavirin for 48 weeks at nine referral hospitals, and evaluated the prognostic factors with a focus on the adherence to the treatment. This study included 68 (55.7%) treatment-naïve patients and 54 (44.3%) patients who did not respond to the previous treatment. Multivariate analysis revealed adherence to peg-IFN and ribavirin as the only significant predictor. Sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Treatment regime, viral factors and host factors were related to the response of PEG IFN treatment. As host factors, younger age, less advanced liver histology, lighter bodyweight, the absence of insulin resistance and absence of alcohol consumption are associated with favorable response to treatment in adult patients . Because these factors tended to be more prevalent in our pediatric subjects than in a comparable population of adults, they conferred advantages in terms of the response to treatment in the present series.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Treatment regime, viral factors and host factors were related to the response of PEG IFN treatment. As host factors, younger age, less advanced liver histology, lighter bodyweight, the absence of insulin resistance and absence of alcohol consumption are associated with favorable response to treatment in adult patients . Because these factors tended to be more prevalent in our pediatric subjects than in a comparable population of adults, they conferred advantages in terms of the response to treatment in the present series.…”
Section: Discussionmentioning
confidence: 75%
“…As host factors, younger age, less advanced liver histology, lighter bodyweight, the absence of insulin resistance and absence of alcohol consumption are associated with favorable response to treatment in adult patients. [44][45][46] Because these factors tended to be more prevalent in our pediatric subjects than in a comparable population of adults, they conferred advantages in terms of the response to treatment in the present series. In general, the findings of liver histology in children with chronic HCV infection were mild or moderate in this study as well as in the previous studies.…”
Section: A Lthough Snp In Il-28bmentioning
confidence: 82%
“…Adherence to interferon and ribavirin has been reported from 54.1% to 95% in different populations (16-18). This wide variation in rate of adherence to anti-HCV medications alone or in combination could be attributed to several factors such as differences in methods of calculating adherence, duration of follow-up, probable confounders of adherence, and socio-cultural and economical features.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies with an increased sample size will be needed in the future. Given that the SVR rate was sharply decreased when adherence to PEG-IFN was below 80% in the treatment of patients with genotype 1 and a high viral load [33], it appears that PSE may not be suitable for patients with genotype 1 requiring a sufficient dose of IFN-based therapy. A previous study [24] indicated that the SVR rate in patients with genotype 1 was 33%, compared to a rate of 100% in patients with genotype 2.…”
Section: Discussionmentioning
confidence: 99%